ANALISIS ISI MESSAGE APPROACH PADA KONTEN LIVE STREAMING AKUN ONLINE SHOP DI TIKTOK SHOP: ANALISIS ISI MESSAGE APPROACH PADA KONTEN LIVE STREAMING AKUN ONLINE SHOP DI TIKTOK SHOP - Gabriella, Devina; Delliana, Santi (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
In the world of commerce, a new trend is developing where selling and promoting products via live streaming on social media platforms is increasingly in demand. TikTok, as one of the main platforms, has launched the TikTok Shop feature which offers live streaming services, becoming a favorite for Indonesian people to shop. Direct interaction between sellers and buyers in live streaming creates a new and interesting shopping experience. The aim of this research is to categorize online stores based on the messaging approach used and evaluate their effectiveness. Qualitative content analysis methods were used in this research. The results show that online stores that use a combined group messaging approach tend to be more effective in attracting live streaming viewers and increasing sales. The four online shop accounts studied fall into three categories of message structuring logic theory. The @louissescarlettfamily account succeeded in attracting many viewers and increasing sales by using an expressive and combinative approach. Meanwhile, the @oktaviana_tas_grosir and @dininrli accounts follow more conventional logic in composing messages, focusing on important information, but are unable to attract many viewers. The @basreng.sultan.bandung account uses an emotional rhetorical approach and is successful in influencing purchasing behavior in live streaming. Thus, online stores that combine expressive and combinative messaging approaches tend to be more successful in attracting audiences and increasing sales. An emotional rhetorical approach can also be effective in influencing purchasing behavior in live streaming. Keywords: Content Analysis, Tiktok Shop, Message Approach